PELUANG BISNIS BARU DI INDUSTRI 5.0 DENGAN IOT, AI, DAN CLOUD COMPUTING - Herwanto, Agus (Jurnal Informasi dan Teknologi, 2025)
The Industry 5.0 is a phase of industrial evolution that emphasises the integration of advanced technologies and human capabilities to create a more efficient and innovative work environment. In this context, technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and Cloud Computing play an important role in creating revolutionary new business opportunities. IoT provides the ability to connect physical devices to the internet, generating real-time data that can be analysed for better decision-making. On the other hand, AI enables automation and intelligent data analysis that can improve productivity and customer experience. Cloud Computing facilitates flexible data storage and processing, allowing businesses to access technology resources without the limitations of physical infrastructure. This article discusses the various business opportunities that arise from the combination of these three technologies, as well as their impact on various industry sectors. By utilising these technologies, companies can create a more adaptive, efficient and sustainable business model in the Industry 5.0 era.